PRZEPISY WYMUSZAJĄCE SWOJE ZASTOSOWANIE W POLSKIM PRAWIE KONSUMENCKIM - Mataczyński, Maciej (Wydział Prawa i Administracji UAM, 2003)
This article deals with the issue of mandatory rules in consumer law. Mandatory rules are those rules of national legal order that are applied to contractual relationships irrespective of the law applicable, as a result of choice of law or indication of connecting factor (also known as lois d’application immediate or Eingriffsnormen). Consumer law is on of the areas of private law where process of harmonization of the Polish law with the EU law is the most advanced. The article contains a survey of Polish laws implementing EU directives on imposed terms in consumer contracts, product liability, consumer credit, contracts concluded outside business premises and distance contracts. The paper examines the way in which the Polish legislator treats mandatory rules. The author includes several specific remarks concerning particular consumer law institutions. In the summary, the author notes certain incoherence between EU directives and their Polish implementation.
REGULATIONS ENFORCING APPLICATION OF EU DIRECTIVES IN THE POLISH CONSUMER LAW